2016
DOI: 10.1038/srep36474
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of basic fibroblast growth factor in streptozotocin-induced diabetic rats: A 1H NMR-based metabolomics investigation

Abstract: The fibroblast growth factors (FGFs) family shows a great potential in the treatment of diabetes, but little attention is paid to basic FGF (bFGF). In this study, to explore the metabolic effects of bFGF on diabetes, metabolic changes in serum and feces were analyzed in the normal rats, the streptozocin (STZ)-induced diabetic rats and the bFGF-treated diabetic rats using a 1H nuclear magnetic resonance (NMR)-based metabolomic approach. Interestingly, bFGF treatment significantly decreased glucose, lipid and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
4
23
2
Order By: Relevance
“…This finding is however in contrast to a more recent (2016) metabolomics study, in which intravenous injection of FGF2 into STZ-induced diabetic rats lowered blood glucose levels 38 . Additionally, to our knowledge, no data describing the effects of central injection of FGF2 in diabetic animals is currently available.…”
Section: Role Of Fgf1 In Glucose Controlcontrasting
confidence: 99%
“…This finding is however in contrast to a more recent (2016) metabolomics study, in which intravenous injection of FGF2 into STZ-induced diabetic rats lowered blood glucose levels 38 . Additionally, to our knowledge, no data describing the effects of central injection of FGF2 in diabetic animals is currently available.…”
Section: Role Of Fgf1 In Glucose Controlcontrasting
confidence: 99%
“…bFGF can reduce structural and functional damage in chronic kidney disease [19], reduce pro-inflammatory signals in acute kidney injury [18] and has tremendous therapeutic potential for diabetes [20,21]. However, it remains difficult to apply bFGF in the clinic because of its short half-life, low stability and poor penetration of the cellular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF plays an important role in the processes involved in cell growth, proliferation, differentiation, survival, and malignant transformation. Numerous studies have demonstrated that bFGF is a pleiotropic cytokine, and exogenous bFGF can promote renal repair in acute kidney injury [18] and reduces pro-inflammatory signals [19], and in chronic kidney disease, it can reduce structural and functional damage [20], and it also has anti-apoptotic activity. However, the concrete mechanism by which bFGF acts remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and animal studies, showing an inverse relationship with body weight and25 adiposity(Lin et al, 2016, Chambers et al, 2018. Interestingly, higher levels of acetate26 in distal colon, which contributes to the regulation of central appetite(Frost et al, 27 2014), are considered more effective than in proximal colon.…”
mentioning
confidence: 99%